Bathymetry Mapping Using Landsat 8 Multyspectral Data of Bangsring Coastal Area - Junika Chintia Ayu Putri; M. Arif Zainul Fuad; M. Arif As’ Adi (Journal Omni-Akuatika, 2018)
The bathymetry map provides information of the seafloor's profile that has diverse in structures, shapes, and topography. Nowadays remote sensing technology becomes more prevalent because it is one of the most effective and efficient methods for bathymetric mapping. This research was aimed to analyze the depth estimation from image processing of Landsat 8 satellite, and measured the water depth using an echosounder. The results showed that the depth of the water in Bangsring was between 0.39 meter and 96.05 meter, and the bathymetric profile continued to decrease with increasing distance. The coefficient determination (R2) and the coefficient correlation (R) were 0.81 and 0.90 respectively with error mean was 19.05%. Based on results, Landsat 8 satellite is suitable and recommended to be used to extract for bathymetric information.